Experimental and theoretical study of Cu2 O photoelectrode and Cu2 O doped with Ag, Co, Ni and Zn metals for water splitting application - Siti Nurul Falaein Moridon,; Mohd Nur Ikhmal Salehmin,; Khuzaimah Arifin,; Lorna Jeffery Minggu,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In the present study, cuprous oxide nanowire fabricated using wet chemical oxidation method was proven to produce high photoactive film for photoelectrochemical (PEC) water splitting. A relatively high photocurrent density of -5mA cm-2 at 0.6V vs Ag/AgCl was generated. The PEC performance is the reflection of intrinsic light absorption capacity at visible region which correspond to 2.0eV, an ideal band gap for PEC water splitting. Comparison with calculated data based on density functional theory using CASTEP shows that the band gap and light absorption capacity obtained from experimental work exhibited a close match. Hence, this study suggested that the preparation of Cu2 O thin film via wet chemical oxidation method obeyed the theoretical prediction. However, the Cu2 O is limited with poor stability in PEC condition attributed to the insufficient potential of its valence band to oxidize water. Therefore, an effort was directed to address the feasibility of shifting the valence band by modeling a doped Cu2 O with several dopants using DFT technique. The selected dopants were Ag, Co, Ni and Zn. Preliminary conclusion of this study indicated that doping could be used to tune the band gap of Cu2 O due to ionic radii of the dopant affected the shifting of band gap. In this study, Co showed more significant improvement of Cu2 O for photoelctrochemical water splitting process. However, to validate the simulation, further study should be carried out experimentally.